First Record of Batrachochytrium dendrobatidis in Pleurodema somuncurense, a Critically Endangered Species from Argentina - Arellano, María Luz (2017)
The presence of Bd zoosporangia in skin samples of the dead individual coming from the eastern warm branch, which reach temperatures of up to 26°C, suggests the occurrence of a Bd strain adapted to higher temperatures (Bd does not grow well above 25°C: Piotrowsky et al. 2004). Since the two pairs of branches differ by almost 4°C, and knowing that temperature may influences patterns of Bd infection, future field-studies should assess the prevalence of the Bd infection in subpopulations of Valcheta Frog inhabiting at different environmental conditions along the stream.